Enfermedad renal crónica: fósforo y su dieta - Nancy J. Gal; Lauren Headrick; Kate Bennett; Wendy J. Dahl (EDIS)
This is a Spanish language version of Chronic Kidney Disease: Phosphorus and Your Diet.